Potential analysis of the republic of Kazakhstan in the customs union - Kulekeyeva, Dinara Zhaxybekovna (KDI School, 2011)
On January 1, 2010, the leaders of Kazakhstan, Russia and Belarus came to an agreement to create the Customs Union. The politicians of three states predict that the Customs Union will be able to become a single currency area with its own supranational currency in the future; this will be the peak integration of the countries into a single trading community. There should be a single economic market formed by the year 2012. In fact, a classic version of the construction of such associations is offered, such associations are wellknown examples of Europe, as well as other regional alliances, like the EU-Turkey Association (signed in 1963), the Arab Common Market (1964), the Central American Common Market (1961), the Organization of Eastern Caribbean States (1991). What are the benefits for the Customs Union participants? The Customs Union is an agreement between States to eliminate duties and the boundaries between them, and to introduce common customs tariff for other states. The aim of the Customs Union’s participants is significant growth of their economies. Kazakhstan’s participation in the Customs Union is an additional factor, which provides its economical and political stability. This will significantly expand the market of well-developed sectors of the economy and revive the ones which have been at a loss. More comfortable and satisfactory conditions will be created for the cross-country flows of capital and work force; this factor will definitely lead to strong economical and social development. The sphere of competition will expand immensely; in the long run this will also have a positive influence on economy overall. It is inevitable and crucial for the Customs union’s participant countries to strengthen cooperation and use it to solve economical, infrastructural and other issues, which require the unity of efforts.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Kazakhstan.